Pemakaian Maslahah Terhadap Konsep Nilai Masa Wang dalam Sistem Perbankan Islam di Malaysia - Ahmad, Ridzwan; Che Seman, Azizi (Jurnal Fiqh, 2009)
The concept of time value of money assumes a particular importance in modern financial system. Even though the concept is deemed substantial justification for the legality of riba, it is widely applied in Islamic banking contracts particularly in the deferred contracts of exchange such as al-bay` bi thaman ajil, ijarah, salam and istisna`. However, it is found that its application in the above said contracts actualizes maslahah for both contracting parties. This fact in turn indicates that justice for both parties is upheld throughout the application of the concept of time value of money in Islamic transaction. This paper analyzes the concept of time value of money in the light of maslahah which serves as the backbone for the exercise of many deferred contracts of exchange. It also emphasizes on some aspects of ambiguity in the operation of Islamic finance particularly in Malaysia. Library method as well as observational method is employed in this paper for data collection. Analytical method is also applied to see whether maslahah which resulting from the application of the concept of time value of money is in line with maqasid al-Syari'ah or otherwise.